New particle formation in coastal New Zealand with a focus on open-ocean air masses - M. Peltola (Atmospheric Chemistry and Physics, 2022)
Even though oceans cover the majority of the Earth, most aerosol measurements are from continental sites. We measured aerosol particle number size distribution at Baring Head, in coastal New Zealand, over a total period of 10 months to study aerosol properties and new particle formation, with a special focus on aerosol formation in open-ocean air masses. Particle concentrations were higher in land-influenced air compared to clean marine air in all size classes, from sub-10 nm to cloud condensation nuclei sizes. When classifying the particle number size distributions with traditional methods designed for continental sites, new particle formation was observed at the station throughout the year with an average event frequency of 23 %. While most of these traditional event days had some land influence, we also observed particle growth starting from nucleation mode in 16 % of the data in clean marine air, and at least part of this growth was connected to nucleation in the marine boundary layer. Sub-10 nm particles accounted for 29 % of the total aerosol number concentration of particles larger than 1 nm in marine air during the spring. This shows that nucleation in marine air is frequent enough to influence the total particle concentration. Particle formation in land-influenced air was more intense and had on average higher growth rates than what was found for marine air. Particle formation and primary emissions increased particle number concentrations as a function of time spent over land during the first 1–2 d. After this, nucleation seems to start getting suppressed by the pre-existing particle population, but accumulation mode particle concentration keeps increasing, likely due to primary particle emissions. Further work showed that traditional NPF events were favoured by sunny conditions with low relative humidity and wind speeds. In marine air, formation of sub-10 nm particles was favoured by low temperatures, relative humidity, and wind speeds and could happen even during the night. Our future work will study the mechanisms responsible for particle formation at Baring Head with a focus on different chemical precursor species. This study sheds light on both new particle formation in open-ocean air masses coming from the Southern Ocean and local aerosol properties in New Zealand.